If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-9n=-n-9-5n
We move all terms to the left:
9-9n-(-n-9-5n)=0
We add all the numbers together, and all the variables
-9n-(-6n-9)+9=0
We get rid of parentheses
-9n+6n+9+9=0
We add all the numbers together, and all the variables
-3n+18=0
We move all terms containing n to the left, all other terms to the right
-3n=-18
n=-18/-3
n=+6
| 5/6*w=7/18 | | 19=3(w+5)-5w | | 539=900-19w | | x/4-7=+ | | b^2-23b+132=0 | | x.5-4=-5 | | 7(x-1)=40 | | 3/8+k=7/8 | | 6x+33=3x+45 | | 5/4(20x+12)=54 | | 16-2(3x-1)=0 | | 4=20x/100 | | 10x+69=109 | | 6(6x+6)-5=6x | | g2–29g=0 | | 6r^2-72r+192=r | | x+9-9=839-9 | | -13(2*x)=13x-26 | | (7-3m)/(m^2-4)=0 | | x-9=830 | | 4c-8-6c=16 | | (x+36)+2x=90 | | 83f-51=51 | | x=32/4*2 | | x-9=8(21) | | 4.4-n=0.06 | | 6x+24-3x=9 | | 5^(6y)=2 | | 72c-72=-0 | | -339.12=18.84j | | 1=0.1x-0.7x-29 | | 5^6y=2 |